P262 Pulmonary benign metastasing leiomyoma: an single-institution case series. (15th November 2017) - Chandarana, K; Rizzo, V; Caruana, EJ; Dawson, AG; Rathinam, S; Nakas, A
Abstract : Introduction: Pulmonary benign metastasizing leiomyoma (BML) is a rare and often asymptomatic presentation of smooth muscle tumour of uterine origin, occurring within the lung. Just over a hundred individual cases have been described in the literature; with two series of ten patients each, from continental Europe and North America. Objectives: We sought to present the first comprehensive descriptive series from a contemporary U.K. population. Methodology: Patients at a single U.K. thoracic surgical centre, between 2003 and 2017, were identified from prospective histology databases. Retrospective data was collected from physical and electronic data sources, and cross-referenced for accuracy. Results: 6 patients – all postmenopausal females – were identified over a 15 year period. Average age was 44±8 years (mean ±SD). Half of the patients were asymptomatic with an incidental finding of pulmonary nodules, whilst the remaining 50% complained of nonspecific respiratory symptomatology. Plain imaging of the chest failed to reveal any abnormality in 2 (33.3%) patients. 5 (88.3%) patients had multiple lesions – median of 9 (range 2 to 12) – with bilateral distribution; measuring a median 11 mm (range 7 to 27) in size on cross-sectional imaging. All patients underwent diagnostic surgical wedge biopsy, with 5 (88.3%) procedures completed thoracoscopically; and no perioperative morbidity. 4 (66.7%) patients had a history of previous hysterectomy, and a further patient underwent a hysterectomy following the diagnosis of BML – all for uterine leiomyomata. 4 (66.7%) patients underwent oophorectomy, whilst one patient required hormonal suppression therapy. Survival was 100% at a median follow up of 37 months (range 4 to 150). Conclusion: BML is a rare clinical entity accounting for a small proportion of patients presenting with pulmonary nodules. Following successful tissue diagnosis, outcomes with conservative or medical management are excellent.